Work Stress and Its Relationships with Employee Marital, Parent-Child and Sibling Relationships during Covid-19 - Haque, Md Fazlul; Hasan, Mohammad Faruk; Shabnam, Mosa Tanjila; Bhawmick, Sojib; Akter, Shamima (South Asian Journal of Social Sciences and Humanities, 2023)
Work stress is a common phenomenon that has multi-dimensional impacts on employee’s private and professional life. It affects employees’ familial, social and other types of relationships. In pandemic situations like Covid-19, work stress is rising to an alarming level. This study aims to determine how stressors such as workload, workplace social support and change in the mode of service during covid-19 contribute to job stress and the relationship between job stress and employee family relationships such as marital, parent-child and sibling relationships. This research was carried out at Dhaka International University and WBB Trust in Dhaka, Bangladesh among 90 respondents. The study was based on a quantitative approach using a survey questionnaire as an instrument and utilized a random sampling method to obtain data. Results show a substantial correlation between work stress and employee marital connection (r=0.753), parent-child relationship (r=0.778), and sibling relationship (r=0.845), according to downhill linear associations. Regression analysis reveals that work stress is significantly correlated to the above employee family relationships with p-value 0.000 (p=0.000<0.05) respectively at 0.05 level of confidence. Recommendations such as further investigation among the government employees, rationalization of work schedules by employers, online and offline stress mitigation programs and real-time online and offline work role and family role awareness sessions were suggested based on the findings. To obtain a more exact response, it is also suggested to undertake additional research using a bigger sample size, a wider scope, and more components.